DIFFICULTIES IN COLLECTING DATA ON DUCTAL CARCINOMA IN SITU AT A POPULATION-BASED CANCER REGISTRY - Freitas-Junior, Ruffo; Lemos, Nayara Alves de Freitas; Moreira, Marise Amaral Rebouças; Silva, Thaysa Cardoso; Oliveira, José Carlos de; Silva, Carleane Maciel Bandeira e (Mastology, 2019)
Objective: To verify data-coding accuracy for ductal carcinoma in situ at the Goiânia population-based cancer registry in the Brazilian state of Goiás. Methods: Ecological time series analysis of cases coded as ductal carcinoma in situ in the state cancer database (ONCOSIS), considering data from the Goiânia population-based cancer registry, from 1994 to 2010. Results: Of 376 cases originally coded as ductal carcinoma in situ, 115 were excluded following a review of the pathology reports. These exclusions referred to cases of lobular carcinoma in situ (n=21), Paget’s disease (n=4), invasive carcinoma (n=08), ductal carcinoma in situ associated with invasive carcinoma (n=14), microinvasive carcinoma (n=21), records on non-residents in Goiânia, and duplicated data (n=46). Conclusion: Many cases needed recoding and, as a consequence, altered the initial database. Standardizing pathology reports and training data collection staff are crucial steps to avoid omissions and errors when transcribing cases of ductal carcinoma in situ in a population-based cancer registry database.